(untitled) (Research, Society and Development, 2022)
With the increasing technological advances in medical equipment, such as CT scanners and angiography, radiation doses from medical exposure are currently the largest source of artificial radiation exposure in the world. These exposures, although justified, must be controlled since, when misused, they can cause risks to exposed individuals. This study consisted of a documentary review of the radiological protection regulations applicable to medical exposures in radiodiagnostic imaging. The method used consisted of a documentary survey carried out in the period 2007-2021 in specific databases of the nuclear field, such as CIN and INIS. The descriptors used were radiological protection, medical exposure, patient exposure to radiation, combined radioprotection, in Portuguese and English. The documents consisted of standards, recommendations, and other technical documents that presented the theme "medical exposure" in the title or keywords, or in their content within the search period. Twenty-three normative documents on the subject were identified, which presented the recommendations, requirements, risks, and radiological protection measures applicable to medical exposures. Medical exposures differ from other forms of radiation exposure, so regulation is essential in controlling these exposures, as well as the qualification of physicians and practitioners of radiological techniques. These professionals must know the risks and benefits of these exposures and understand and implement the principles of radiation protection for patients. This article aims to provide the theoretical background to assist them in this process.